Gladiolus adanus (Iridaceae, Crocoideae), a new species from Türkiye - Eker, İsmai̇l; Sağiroğlu, Mehmet (Phytotaxa, 2024)
Gladiolus adanus is introduced to the scientific world as a new species from Adana/Tufanbeyli/Türkiye. In this study, description and illustration, diagnostic morphological characters, habitat, distribution, ecological characteristics, conservation status, seed micromorphological characters (LM and SEM) and comparisons with close species are given.